2017
DOI: 10.1097/ta.0000000000001618
|View full text |Cite
|
Sign up to set email alerts
|

The rate of deep vein thrombosis doubles in trauma patients with hypercoagulable thromboelastography

Abstract: Prognostic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 33 publications
2
93
1
3
Order By: Relevance
“…Acceleration of TEG R time in trauma subjects correlates with deep vein thrombosis (DVT). Brill et al demonstrated that trauma patients with hypercoaguable TEG on admission have higher rates of DVT than those that do not (15.6% vs 8%, P = .039) . Selby et al studied the coagulation markers thrombin, prothrombin, and soluble fibrin at different time points in trauma subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acceleration of TEG R time in trauma subjects correlates with deep vein thrombosis (DVT). Brill et al demonstrated that trauma patients with hypercoaguable TEG on admission have higher rates of DVT than those that do not (15.6% vs 8%, P = .039) . Selby et al studied the coagulation markers thrombin, prothrombin, and soluble fibrin at different time points in trauma subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, blood samples from patients with hypercoaguable TEG on admission have higher rates of DVT than those that do not (15.6% vs 8%, P = .039). 16 Selby et al studied the coagulation markers thrombin, prothrombin, and soluble fibrin at different time points in trauma subjects. They found that soluble fibrin was increased in those who developed DVT compared with those who did not.…”
Section: Heparin Reverses the Procoagulant Effect Of Cctsmentioning
confidence: 99%
“…The MA value of rapid TEG is also an independent predictor of pulmonary embolism (44,45). Other studies have reported that CI had a predictive value for deep venous thrombosis and thrombosis in prostate cancer (46,47). Furthermore, the TEG method simulates the entire process of venous thrombosis ex vivo , and, therefore, the CI value can reflect a composite index of venous thrombosis formation.…”
Section: Discussionmentioning
confidence: 82%
“…This is partially attributable to conventional labs that assess coagulation lacking an ability to detect hypercoagulability. However, whole blood viscoelastic hemostatic assays (VHA) has been shown to predict thrombotic complications in trauma patients, 3,4 liver disease patients, 5 cardiac surgery patients, 6 inflammatory bowel disease patients, 7 and malignancy. 5,8 This is further supported by patients presenting with new onset deep vein thrombosis having hypercoagulable VHA values compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…46,8 Clot strength is a function of both fibrinogen and platelets. 10 However, the majority of clot strength is attributable to platelets, 11 which continue to evolve as an important process driving thrombotic complications in patients in the intensive care unit.…”
Section: Introductionmentioning
confidence: 99%